(Just) a walk with the dog? Animal geographies and negotiating walking spaces. (17th February 2018) - Fletcher, Thomas; Platt, Louise
Abstract: In this paper, we present findings from interviews conducted with people who walk with dogs. Drawing on new walking studies and animal geographies as our theoretical framework, we adopt the view that walking is more than just walking; it is often a highly sensual and complex activity. We argue that walking with dogs represents a potentially important cultural space for making sense of human–animal relations. We show how the personalities of both dog and walker can shape not only walking practices, but also the human–animal bond. We contend that the walk is a significant arena where relations of power between animal and human are consciously mediated. We also provide evidence which indicates the contested nature of walking practices and spaces. We conclude that the dog walk is a useful practice through which to examine human–animal relations and thus to contribute to the field of animal geographies.